RISK OF POST STROKE PNEUMONIA DURING HOSPITALIZATION (Jurnal Mitra Kesehatan, 2021)
Introduction: Post-stroke pneumonia is the most a common complication during the first few weeks after a stroke. Thus, a score is needed for the early identification of stroke patients with an increased risk of pneumonia to assist the nursing team in preventing the onset of pneumonia in stroke patients during hospitalization. This study aimed to assess the application of the A2DS2 score to predict pneumonia in acute ischemic stroke patients. Method: This is a diagnostic study that used a cross-sectional method conducted among adult acute ischemic stroke patients. Data analysis was performed to assess the calibration and discrimination performance of the A2DS2 score. Results: A total of 16 respondents were followed up. The incidence of post-stroke pneumonia was observed in 6 patients (37.5%). Conclusion: This scoring proved clinically accurate to predict the incidence of pneumonia in acute ischemic stroke patients.